Winter management for steer calves on a wintering, grazing, and fattening program. - Smith, E.F.; Koch, B.A.; Cox, R.F.; Walker, G.L. (Kansas Agricultural Experiment Station, 2011)
Dry bluestem pasture has been used successfully several years at this station as a source of winter roughage for steer calves that are to be grazed during the summer and sold off grass as feeder or stocker yearlings. This is the first attempt to supplement dry grass during the winter with several pounds of grain combined with protein, in an effort to attain sufficient winter gain so the calves could be finished on grain in the late summer and sold as fat yearlings The test is to determine if dry grass can be supplemented in such a manner that calves will compare favorably in total performance with steer calves wintered on good-quality roughages. The steers will be grazed until August 1 on bluestem pasture, then fattened in dry lot to choice grade.
Keywords: Beef; Management; Protein; Gain